Diagnostic assessment of students’ numeracy ability in phase a using the finger math method: Analysis of patterns of accuracy and speed of answer - Asma, Andi; Tahir, Muhammad (Jurnal Prima Edukasia, 2026)
This study aims to conduct a diagnostic assessment of Phase A students' numeracy skills through multivariate analysis of the pattern of accuracy and speed of answers using the Finger Math method. This study is based on the still low numeracy skills of Madrasah Ibtidaiyah students and the dominance of conventional learning approaches that pay less attention to aspects of the student's numeracy process. This study uses a quantitative approach with a quasi-experimental design in the form of a factorial design. The research sample consisted of 100 second-grade students of Madrasah Ibtidaiyah (Phase A) in Manado who were divided into an experimental group (Finger Math) and a control group (conventional). Data were collected through a numeracy test and analyzed using One-Way MANOVA. The results of the study show that the Finger Math method has a significant simultaneous effect on the accuracy and speed of calculation (Wilks’ Lambda = 0,045; p < 0,001). Further univariate ANOVA tests showed a very significant effect on counting accuracy (F = 830,277; p < 0,001) and counting speed (F = 1.094,872; p < 0,001). Descriptively, students learning with Finger Math demonstrated higher accuracy and faster completion times than the conventional group. These findings confirm that Finger Math is effective as both a learning strategy and an initial diagnostic assessment for comprehensively mapping the numeracy profiles of Phase A students.